Effect of the roasting conditions on the physicochemical, quality and sensory attributes of coffee-like powder and brew from defatted palm date seeds - Ahmed, Mohamed Fikry Mohamed; Yusof, Yus Aniza; Al-Awaadh, Alhussein M.; Abdul Rahman, Russly; Chin, Nyuk Ling; Mousa, Esraa; Chang, Lee Sin (MDPI, 2019)
Developing a bioactive brew is a novel track for revalorization of palm date byproducts. The effect of roasting temperature (160, 180 and 200 °C ) and roasting time (10, 20 and 30 min) on the hardness of the roasted date seeds, moisture content of the defatted roasted date seed powder (DRDSP), bulk density of the DRDSP, color parameters of DRDSP, quality attributes (extraction yield, pH and browning index), the chemical properties (antioxidants and total phenolic content) and the sensory attributes (color, aroma, taste and overall preference) of the brew prepared from DRDSP was studied. The physicochemical, quality, and sensory attributes were found to be significantly influenced by the roasting temperature and time. Additionally, the models proposed could satisfactorily describe the changes in the different properties during the roasting process. The optimum conditions of the roasting process obtained using the superimposed contour plot were 199.9 °C and 21.5 min. In the longer term, the results of this study would be beneficial for the manufacturers of the date seeds powder and brew.